Toward Quality Culture in Nepalese Higher Education: A Systematic Review of QMSS in Affiliated Colleges - Gautam, Tara Prasad; Mishra, Anjay Kumar; Shailashri , V T (Intellectual Journal of Academic Research, 2025)
Purpose This study systematically reviews Quality Management Support Systems (QMSS) in Nepalese higher education, focusing on affiliated colleges under public universities. It examines existing quality assurance (QA) frameworks, identifies challenges, compares Nepal’s QA practices with India, Malaysia, and Bangladesh, and explores factors shaping a quality culture. Methods Following PRISMA guidelines, a systematic review was conducted using academic databases and official policy documents up to 2025. Sources addressing QA in Nepalese affiliated colleges were selected. Data were thematically analyzed, resulting in five themes: QA readiness, accreditation, internal QA, stakeholder involvement, and the policy–practice gap. Findings Nepal has formal QA and accreditation systems, but implementation is inconsistent. Affiliated colleges face unclear policies, limited resources, and fragmented governance. Accreditation is often viewed as compliance rather than continuous improvement. Internal Quality Assurance Cells exist but are underused, and stakeholder participation is low. Comparison suggests Nepal could benefit from India’s structured accreditation, Malaysia’s national QA integration, and Bangladesh’s focus on internal QA. Conclusions Nepal’s affiliated colleges need clearer QA mandates, capacity building, stronger stakeholder engagement, and incentive-linked accreditation. Shifting from compliance to continuous improvement is key to developing a quality culture.